2018
DOI: 10.1126/scitranslmed.aar2749
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic neurological consequences of early-life Zika virus infection in mice

Abstract: Although congenital Zika virus (ZIKV) exposure has been associated with microcephaly and other neurodevelopmental disorders, long-term consequences of perinatal infection are largely unknown. We evaluated short- and long-term neuropathological and behavioral consequences of neonatal ZIKV infection in mice. ZIKV showed brain tropism, causing postnatal-onset microcephaly and several behavioral deficits in adulthood. During the acute phase of infection, mice developed frequent seizures, which were reduced by tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 56 publications
7
71
2
2
Order By: Relevance
“…These findings as well as the smaller cerebellum GM volumes may explain the increased incidents of balance loss seen amongst the ZIKV-infected infant RMs during their exploration of a novel social environment. Although we did not perform a specific test of gross motor function, our current findings of uncoordinated movements resulting in losses of balance suggest that postnatal ZIKV infection may have impacted motor development and psychomotricity, which has also been demonstrated in a murine model of postnatal ZIKV infection 71 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These findings as well as the smaller cerebellum GM volumes may explain the increased incidents of balance loss seen amongst the ZIKV-infected infant RMs during their exploration of a novel social environment. Although we did not perform a specific test of gross motor function, our current findings of uncoordinated movements resulting in losses of balance suggest that postnatal ZIKV infection may have impacted motor development and psychomotricity, which has also been demonstrated in a murine model of postnatal ZIKV infection 71 .…”
Section: Discussionmentioning
confidence: 62%
“…There have been conflicting reports on the neurologic complications and neurodevelopmental outcomes of children exposed to ZIKV in the peripartum and postnatal periods [26][27][28][29][30] . Studies with large numbers of cases have yet to be published, while research in animal models suggest that ZIKV infection during the postnatal period may also have a deleterious impact on development 31,32 . We recently demonstrated in infant rhesus macaques (RMs) that postnatal infection with ZIKV disseminates to the central and peripheral nervous systems with histologic features in the post-mortem brain similar to prenatal ZIKV infection 31 .…”
Section: Mainmentioning
confidence: 99%
“…To study these questions on Zika virus pathogenesis, various animal models have been developed, most of which use immune deficient mice that are susceptible to Zika virus infection in vivo such as A129 (129 background, deficient in IFN-α/β receptor), AG129 (129 background, deficient in IFN-α/β and IFN-γ receptors), A6 (C57/BL6 background, deficient in IFN-α/β receptor), AG6 (C57/BL6 background, deficient in IFN-α/β and IFN-γ receptors); Stat2 deficient mice, and Rag1 deficient mice (13,2730). Zika virus can also infect wild type neonatal mice and cause diseases that resemble to some extent microcephaly, paralysis, and seizure (3133). Mechanistically, these neurological manifestations have been linked to Zika virus infection of neuron progenitor cells and other neurocytes in neonatal mice in vivo (11,17,34).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that ZIKV replicates in human neural progenitor cells and brain organoids, resulting in cell death and cell cycle arrest (7, 8). Both intra-uterine and neonatal ZIKV exposure in mice was shown to compromise neurogenesis and cause severe necrosis in different brain regions, along with persistent viral replication and widespread neuroinflammation (9, 10). Moreover, it was shown that activation of microglial cells and astrocytes associated to viral replication in the brain affects cognitive function and the differentiation of glial progenitors cells impairing brain development (11, 12).…”
Section: Introductionmentioning
confidence: 99%